Tafsir Anti-Kolonial di Indonesia - Usan Usan; Tatang Muslim Tamimi (UIN Sunan Gunung Djati Bandung, 2021)
This paper aims to examine the anti-colonial commentators and their responses, styles, and thoughts. This research method uses descriptive-analytical. The results and discussion of this paper include interpretive scholars including Ahmad Hasan, Ahmad Sanusi, and Mahmud Yunus. The characteristics of the anti-colonial interpretation are familiar to the socio-political conditions. The result of this creation is because it is located at a time before independence, possibly in the explanation there are not many verses that hold the impetus that arises in the power of endeavors such as those contained in Surah Al-Baqarah: 85 and At-Taubah: 71, in ensuring that The results of the interpretation of the creation at that time have a relationship with the socio-political matters that are in place, moreover it can be more specific to the responses to problems that exist from the results of the interpretations at that time, namely colonized conditions, coupled with other problems such as internal problems which are intertwined with Indonesian citizens who arose a variety of activities from community organizations for the struggle for independence.